Development and performance evaluation of cocoa pod breaker cum bean extractor - ARUN JOSHY GEETHU S KRISHNENDU K. M NIKHIL C. S; Er. Rajesh G. K (Guide) (Tavanur 2015 Department of Food and Agricultural Process Engineering)
Cocoa is a tropical crop and native to Aamazon region of South America. The developed cocoa pod breaker cum extractor had two main parts: cocoa pod breaker and cocoa bean extractor.
Development and performance evaluation of cocoa pod breaker cum bean extractor